ARE POST-SEISMIC EFFECTS OF THE M = 8.4 BOLNAY EARTHQUAKE (1905 JULY 23) STILL INFLUENCING GPS VELOCITIES IN THE MONGOLIA-BAIKAL AREA? - Calais E.; Vergnolle M.; Déverchère J.; San'kov V.; Lukhnev A.; Amarjargal S. (My University, 2002)
GPS measurement campaigns in the Mongolia-Baikal area show that: (1) the Baikal rift zone is currently opening at 4-5 mm yr-1 in a NW-SE direction and (2) the western part of the Amurian-north China block is moving eastward relative to Eurasia at 5-7 mm yr-1 . These results are consistent with recent geodetic studies in Asia, and indicate that crustal motions in Mongolia and north China derived from geodetic measurements are significantly faster than those proposed by most deformation models of Asia. Using a numerical model, we test whether post-seismic deformation caused by viscoelastic relaxation in the lower crust following the Tsetserleg-Bolnay earthquake sequence (M w = 7.9 and 8.4, 1905 July) can explain this discrepancy. We find that surface velocities at the GPS sites presented here for the 1997-2000 time period can reach 4 mm yr-1 , depending on the earthquake source parameters and the rheology used in the models. Using a model based on our best current knowledge of lithospheric structure and rheology in the Mongolia-Baikal area, we find that the contribution of post-seismic effects to the GPS velocities presented here is less than 2 mm yr-1 for the Mongolian sites and less than 1 mm yr-1 for the Baikal sites. We therefore conclude that the post-seismic effects of the M w = 8.4, 1905 Bolnay earthquake cannot explain why the GPS-derived crustal motions in Mongolia and the Baikal rift zone are significantly larger than those proposed by deformation models of Asia. This discrepancy must therefore be sought in processes not accounted for in most of these deformation models, such as the far-field contribution of the Pacific subduction zones and/or the effect of gravitational forces on intracontinental deformation.
Keywords: Asia; GPS; postseismic deformation